Development of Virtual Reality Application for Arachnophobia Using Multimedia Development Life Cycle Method - Anggoro, Nugroho Ari; Astuti, Ika Asti (Journal of Information Systems and Informatics, 2024)
Arachnophobia or known as irrational fear of spiders, can be detrimental to one’s health and overall well-being. Common procedures, such as Cognitive Behavioral Therapy or medication, are often inefficient and take a lot of time to demonstrate results, thus the alternative way of dealing with arachnophobia is urgently needed. Such alternatives can be achieved by utilizing Virtual reality technology, hence the purpose of the following research is to address the matter by developing Virtual reality based application with the help of Multimedia development life cycle method. The MDLC method was chosen due its ability to create multimedia application, and the collected results of the experiment demonstrate that indeed MDLC can be used as a method to develop the arachnophobia therapy application that is both time efficient and works as test shows the decreasing time used for use application as well as two respondents that able to be detected for having arachnophobia. In conclusion the application developed using MDLC is indeed able to be an alternative way of arachnophobia therapy.